3(3c-1)-16=7c+3

Simple and best practice solution for 3(3c-1)-16=7c+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3c-1)-16=7c+3 equation:


Simplifying
3(3c + -1) + -16 = 7c + 3

Reorder the terms:
3(-1 + 3c) + -16 = 7c + 3
(-1 * 3 + 3c * 3) + -16 = 7c + 3
(-3 + 9c) + -16 = 7c + 3

Reorder the terms:
-3 + -16 + 9c = 7c + 3

Combine like terms: -3 + -16 = -19
-19 + 9c = 7c + 3

Reorder the terms:
-19 + 9c = 3 + 7c

Solving
-19 + 9c = 3 + 7c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7c' to each side of the equation.
-19 + 9c + -7c = 3 + 7c + -7c

Combine like terms: 9c + -7c = 2c
-19 + 2c = 3 + 7c + -7c

Combine like terms: 7c + -7c = 0
-19 + 2c = 3 + 0
-19 + 2c = 3

Add '19' to each side of the equation.
-19 + 19 + 2c = 3 + 19

Combine like terms: -19 + 19 = 0
0 + 2c = 3 + 19
2c = 3 + 19

Combine like terms: 3 + 19 = 22
2c = 22

Divide each side by '2'.
c = 11

Simplifying
c = 11

See similar equations:

| 1/4(7680) | | x+15+x+15+x+x=x+45+x+40+x+25 | | 7/6*x/42 | | 7x+35=2x+140 | | (-28x^12y^5)^1/2 | | 0=(x-2) | | -6y+18=-24 | | 42/7*x/6 | | j(x+yj)+2(x-yjh)+1-j=0 | | 16z=48 | | -30-(-51)=x/8 | | x-53=15 | | 4(2c+4)=48 | | y^4-2y+y=0 | | 62.34=k-10.7 | | 4x(2c+4)=48 | | 2x+3y=0.67 | | 2m-2s-1=1 | | x/x-12=4 | | 2n-6=8(8n+6)+8 | | jz+2z+1-j=0 | | x+43=119 | | -.5(32)*x^2+16x=2.56 | | 9+3(z-3)=-5z+5 | | 3-8(1+9z)=15 | | .5(32)*x^2+16x=2.56 | | 72/6x | | g(x)=-(2/3)^x= | | -7(n+4)+31=-4n-12 | | -6(x-3)=-12 | | 4/15x-5 | | 5t=32 |

Equations solver categories